Analytical Methods on Computational Capabilities of Multi-parameter Natural Algorithm - Li Jianhua; Wei Xing (2014 Seventh International Symposium on Computational Intelligence and Design, 2014)
Concerning the Computational capabilities of Multi-parameter natural algorithm, the Mathematical statistical analysis method using multi-indicators has been proposed. These indicators include the calculation central tendency, the dispersion trends and data distribution, which can clearly reflect the natural algorithm computational capabilities for specific problems, and reveal the influence of different parameters on the process of algorithms calculation. Finally, the immune clone operator is taken as an Analysis case. The experimental data has given the rule of the influence of computing power in different parameters.